2012
DOI: 10.1007/s11547-012-0905-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of abdominal aortic aneurysms: 6 years of experience at a single centre

Abstract: Consistent with the literature data, our study confirms the safety and long-term efficacy of EVAR for treating AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…During the study period we treated, elective and emergency, intravascularly, a total of 270 patients with AAA [17], 60 patients with TAA [18], and 36 patients with isolated iliac aneurysms [19].…”
Section: Methodsmentioning
confidence: 99%
“…During the study period we treated, elective and emergency, intravascularly, a total of 270 patients with AAA [17], 60 patients with TAA [18], and 36 patients with isolated iliac aneurysms [19].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies (17/27 studies with a total of 6770 participants) did not specify the type of AAA or reported only that participants had 'abdominal aortic aneurysm'. 40,41,67,69,[72][73][74][76][77][78][79][80][81][82][86][87][88][89][90] In four studies, participants (total of 898) were reported to have infrarenal AAAs; 70,71,84,85 in two studies participants (total of 295) were reported to have iliac artery aneurysms; 66,83 in two other studies, participants (total of 195) were reported to have asymptomatic aneurysms; 77,79 in three studies, participants (total of 45) were reported to have symptomatic aneurysms; 75,77,79 and, in two studies, participants (total of 39) were reported to have ruptured AAAs. 68,75…”
Section: Length Of Follow-upmentioning
confidence: 97%
“…The 22 cohort studies published in full were of mixed quality (Figure 3). 40,41,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] The individual study-level results are detailed in Appendix 6. For the majority of studies, over half or more of the ReBIP criteria were not met, or the information provided in the studies was insufficient to determine if the criteria were met, and were, therefore, judged as being of low or moderate quality.…”
Section: Cohort Studiesmentioning
confidence: 99%
See 2 more Smart Citations